1994
DOI: 10.1063/1.467227
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow temperature kinetics of neutral–neutral reactions. The technique and results for the reactions CN+O2 down to 13 K and CN+NH3 down to 25 K

Abstract: An entirely new experimental method is described which enables the rate constants of neutral–neutral gas-phase reactions to be measured at ultralow temperatures. The measurements are made by applying the pulsed laser photolysis (PLP), laser-induced fluorescence (LIF) technique of studying the kinetics of free radical reactions in the ultracold environment provided by the gas flow in a Cinétique de Réaction en Ecoulement Supersonique Uniforme (CRESU) apparatus. The experimental method is described in some detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
219
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(238 citation statements)
references
References 60 publications
10
219
0
5
Order By: Relevance
“…The gas flow did not encounter the walls of the 115 chamber, avoiding condensation problems, and the residence time in the flow was long enough to monitor a chemical reaction. The technique, known as CRESU (Cinétique de Réaction en Ecoulement Supersonique Uniforme), was initally used to measure rate coefficients for ion-molecule reactions 14 , 120 but its application was extended to the study of neutral-neutral reactions by Rowe, Sims and Smith, who generated freeradicals using laser flash photolysis (LFP) and monitored their temporal decay using laser-induced fluorscence (LIF) spectroscopy 1, 15,16 or by chemiluminescence. 17,18 The method 125 has enjoyed considerable success, and has been extensively reviewed.…”
mentioning
confidence: 99%
“…The gas flow did not encounter the walls of the 115 chamber, avoiding condensation problems, and the residence time in the flow was long enough to monitor a chemical reaction. The technique, known as CRESU (Cinétique de Réaction en Ecoulement Supersonique Uniforme), was initally used to measure rate coefficients for ion-molecule reactions 14 , 120 but its application was extended to the study of neutral-neutral reactions by Rowe, Sims and Smith, who generated freeradicals using laser flash photolysis (LFP) and monitored their temporal decay using laser-induced fluorscence (LIF) spectroscopy 1, 15,16 or by chemiluminescence. 17,18 The method 125 has enjoyed considerable success, and has been extensively reviewed.…”
mentioning
confidence: 99%
“…Low temperatures were achieved via the isentropic expansion of a buffer gas (argon in this study) through a suitably designed Laval nozzle. The resulting supersonic flow was found to be axially and radially uniform in temperature, density and velocity [Sims et al, 1994] In conclusion, the ratio kc•/a/ko should be decreased by a factor of 0.8 in the Krasnopolsky and Cruikshank [1995] model, which will only slightly increase the yield of HCN. Although, the efficiency of HCN production should not be revised for Triton's atmosphere, it is worthwhile to include the results of our work, in addition to the study by Canosa et al.…”
Section: Methodsmentioning
confidence: 99%
“…The fundamentals of the CRESU technique have been described in detail previously [Sims et al, 1994]. Only the essential features of the experiment, therefore, will be reported here.…”
Section: Methodsmentioning
confidence: 99%
“…Uniform supersonic flow systems have been developed and applied with great success for kinetics studies at low temperatures, as demonstrated by the CRESU technique (a French acronym for Reaction Kinetics in Uniform Supersonic Flows), 7,[14][15][16] and several subsequent instruments modeled after it. [17][18][19][20][21] At the heart of these systems is a Laval nozzle, an axisymmetric convergent-divergent nozzle recognizable as the familiar rocket nozzle design, from which emerges a flow uniform in temperature, velocity, and density along the propagation axis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a new technique is sought that will overcome these challenges and allow unimolecular and bimolecular reactions to be probed for large polyatomic systems such that branching ratios and vibrational distributions can be accurately determined, transient reaction intermediates characterized, and reaction kinetics measured with product identification and branching. To this end, we have developed a new instrument based on a uniform supersonic flow system 7 combined with a chirped-pulse Fourier transform microwave (CP-FTMW) spectrometer. [8][9][10][11][12][13] This chirped-pulse, uniform flow (CPUF) instrument can record ultra-broadband rotational spectra at MHz resolution for transient and rotationally thermalized reaction products.…”
Section: Introductionmentioning
confidence: 99%